Photocurable Stretchable Conductors with Low Dynamic Resistance Variation - Huang, Chun-Yung; Lai, Yi-Chin; Liao, Ying-Chih (ACS applied electronic materials, 2019)
A simple and facile method is developed to prepare photocurable conductive resin for stretchable conductors. To prevent substrate damages, intense pulsed light (IPL) technology was introduced to simultaneously cure photoresins and sinter the silver nanomaterials at room temperature. During the IPL illuminating, the intense pulsed light not only can heat the silver nanomaterials locally but also cure the polymeric resin at the same time. Compared to a regular curing–heating process, this process can form a more effective conductive pathway with a low percolation threshold. The high aspect ratio of AgNWs makes its own low percolation threshold of only 10 wt %. A lower percolation threshold can not only save the amount of expensive conductive materials but also retain the stretchability of elastomer. The combination (AgNWs/Ag flakes) as conductive fillers can maintain great electrical conductivity during the stretching process with only 25 wt % loading of silver. The resistance ratio became only 1.5 times the original under 60% strain. The fast curing and sintering process, low bulk resistivity, and good stretchability of the photocurable resins show great potential for wearable printed electronics.